2021
DOI: 10.1108/tpm-11-2020-0097
|View full text |Cite
|
Sign up to set email alerts
|

Shared leadership and team creativity: a team level mixed-methods study

Abstract: Purpose This paper aims to conduct two studies to investigate shared leadership and team creativity (TC) in leaderless short-term project teams (STPTs). Design/methodology/approach To answer the research question, this paper used a multi-level mixed-methods design. This paper analyzed video recordings, transcripts of STPTs’ collaboration and self-report surveys from an international engineering competition. In Study 1, this paper attempted to connect relation-oriented shared leadership (ROSL) and task-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Secondly, the paper provides a fine-grained view of the specific leadership behaviours amenable to sharing in organisational teams. Evidence from studies of student teams suggests that both task and relations-oriented leadership behaviours can be shared (Xie et al , 2021) but little has been revealed about how such behaviours are exhibited in field settings or what leadership functions are fulfilled. This paper sheds light on SL, as it emerges from the daily interactions of team members in authentic organisational contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the paper provides a fine-grained view of the specific leadership behaviours amenable to sharing in organisational teams. Evidence from studies of student teams suggests that both task and relations-oriented leadership behaviours can be shared (Xie et al , 2021) but little has been revealed about how such behaviours are exhibited in field settings or what leadership functions are fulfilled. This paper sheds light on SL, as it emerges from the daily interactions of team members in authentic organisational contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Aubé et al (2018) concluded that shared leadership can improve team functioning, thus predisposing members to attain the highly gratifying and productive flow state. By accepting the "nagging" the football players in the currents study also took on a role in contributing to the ideas in a more detailed manner and thereby accepting a shared leadership (Duguay et al, 2020) by taking on the players part of the responsibility shared leadership is associated with team creativity (Xie et al, 2021) and team reflexivity (Hadi and Chaudhary, 2021).…”
Section: Resultsmentioning
confidence: 97%
“…Studies on shared leadership in virtual teams confirm that teams benefit more from shared leadership than hierarchical leadership, especially in terms of performance (Drescher and Garbers, 2016; Hoch and Dulebohn, 2017; Hoch and Kozlowski, 2014; Hoegl and Muethel, 2016; Nordbäck and Espinosa, 2019; Muethel et al , 2012; Pearce et al , 2004). In addition, single studies recognized that in virtual teams shared leadership has a positive effect on satisfaction (Robert and You, 2018), a positive effect on creativity (Han et al , 2020; Xie et al , 2021) and a positive effect on the sense of belonging to a group and the fair distribution of responsibility and workload (Yilmaz et al , 2020).…”
Section: Introductionmentioning
confidence: 99%